Plasmonic Efficiency Enhancement of High Performance Organic Solar Cells with a Nanostructured Rear Electrode. Issue 2 (13th September 2012) - Niesen, Bjoern; Rand, Barry P.; Van Dorpe, Pol; Cheyns, David; Tong, Lianming; Dmitriev, Alexandre; Heremans, Paul
<x xml:space="preserve">Abstract</x> A strategy and implementation for efficiency enhancement of optimized high performance organic solar cells by a plasmonic nanostructured Ag rear electrode is presented. This enhancement is achieved by tuning the surface plasmon resonance of the nanostructures to the active layer absorption tail, which generates enhanced absorption by light scattering, as verified by experiment and simulation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>